2021
DOI: 10.3389/fsufs.2021.720700
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Edible Food Packaging in Slovakia: A Case Study on Young Generation

Abstract: The increasing problem of plastic pollution from food packaging created a new market potential for inventing environmental-friendly packaging in the food market including edible food packaging. The main objective of the study was to identify attitudes and perceptions of young people toward edible food packaging. Primary research was conducted via a questionnaire survey. The research sample involved 22 respondents between 19 and 30 years from Slovakia. A questionnaire survey was interconnected with sensory anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Horska et al. (2021) used a sample of young consumers to test the acceptability of 23 samples of edible packaging without their respective food products and found that gender did not play a role in liking. Similarly, in this study of 100 general population consumers with a diverse set of demographics, there were no significant differences in liking of the products in their edible packages by age, gender identity, education, or income except the muffin in the edible liner, which was liked less only by those with a high school education or less.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horska et al. (2021) used a sample of young consumers to test the acceptability of 23 samples of edible packaging without their respective food products and found that gender did not play a role in liking. Similarly, in this study of 100 general population consumers with a diverse set of demographics, there were no significant differences in liking of the products in their edible packages by age, gender identity, education, or income except the muffin in the edible liner, which was liked less only by those with a high school education or less.…”
Section: Discussionmentioning
confidence: 99%
“…One of the emerging solutions to reducing single-use plastic waste is the use of edible food packaging. Edible food packaging is made of edible materials, which can be cast into a film and then engineered into different forms, such as pouches, wraps, or liners (Horská et al, 2021). The food packaging industry is also consistently trying to utilize food processing byproducts and to develop circular bioeconomy and carbon neutrality (Cristofoli et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Recent development in active and smart food packaging focuses on biobased and biodegradable polymers with various additives (nanoparticles, plant extracts and more [ 4 , 5 , 6 , 7 ]). Edible food packaging can be considered a thin layer on the surface of the food product, so that pollution and waste do not occur when eaten with food, usually applied on product by spraying, dipping or wrapping [ 5 ]. Edible electrospun packaging materials are usually made of polysaccharides, proteins, lipids or combinations of them [ 1 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methods including controlled atmosphere storage, low temperature and edible coating are available to extend the shelf life and maintain the quality of post-harvest vegetables. The consumer acceptability of the addible food coating has increased in recent decades and is used widely around the globe [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%